Knowledge, attitudes and beliefs related to HIV/AIDS among adolescents in Malaysia - Zulkifli, S.N.; Wong, Y.L. (Malaysian Medical Association, 2002)
Findings on knowledge, attitudes and beliefs related to HIV/AIDS among 520 Malaysian adolescents, aged 15 to 21 years, based on a survey conducted in Peninsular Malaysia showed that the average score for knowledge on HIV/AIDS was high, and majority showed a positive attitude towards the disease. However, misconceptions regarding transmission and gender bias related to sexual behaviour and contracting the disease prevailed. Although 72 percent of the sexually-experienced did not use protection at first sexual intercourse, 80 percent did not perceive themselves to be at risk of contracting HIV/AIDS. A critical review of existing HIV/AIDS prevention programmes to focus on adolescent risk-taking behaviour and sexuality issues, including male-female negotiation skills, is warranted.